Synthesis, crystal structure and luminescence properties of a cadmium(II) complex based on 2-hydroxy-6-methylisonicotinic acid - Zhang, T.; Tian, A.Q.; Feng, X.; Ng, S.W.; Tian, P.H.; Wang, Y. (Fujian Institute of Research of the Structure of Matter, 2016)
A new cadmium(II) complex [Cd(Hminic)(IP)]n (1, Hminic = 2-hydroxy-6-methylisonicotinic acid, IP = imidazo[4,5-f]-1,10-phenanthroline), has been synthesized by the reaction of a Hminic and auxiliary N-containing ligands with Cd(II) ion under hydrothermal conditions. The complex was studied by elemental analysis, IR spectroscopy and X-ray crystallography. It is formulated as C20H13CdN5O3, crystallizes in monoclinic system, space group C2/c with α = 9.6764(8), b = 26.767(2), c = 14.1332(11) Å and β = 97.4510(10)°. V = 3629.7(5) Å3, Z = 8, Mr = 483.75, Dc = 1.770 g/cm3, F(000) = 1484 and μ = 1.237 mm-1. The final refinement gave R = 0.0309 and wR = 0.0703 for 4151 reflections with I > 2σ(I). In the structure of 1, two Cd(II) atoms are joined by a pair of μ2-hydroxyl oxygen atoms giving rise to a dinuclear Cd(II) unit which is bridged by Hminic linkers to form a 1D ladder-like polymer chain. The chelating ligand IP coordinated to the Cd(II) atom, and alternately attached to both sides of the ladder-like polymer chain. Adjacent chains are further bound together by strong intermolecular hydrogen bonds and face-To-face φφ interactions, resulting in the formation of a 3D supramolecular architecture. Furthermore, the thermal stability and luminescent properties of this complex and the free ligands have been investigated.